Effects of supplementary vegetable and animal fats on the slaughter values of fatteners, meat quality, and fatty acid profile in pigs - D. Lisiak; E. Grześkowiak; K. Borzuta; S. Raj; P. Janiszewski; G. Skiba (Czech Journal of Animal Science, 2013)
The study was conducted on 32 hybrids of (Polish Large White × Danish Landrace) × Duroc breeds fed similar energy content feed, however differing in fat diet supplements. The animals were divided into four groups in which the following fat supplements were added to the feed: A - rapeseed and linseed oils, B - rapeseed and fish oils + swine fat, C - linseed and fish oils, D - rapeseed and linseed oils + lard. The carcass slaughter value was estimated and physicochemical and sensory traits of longissimus lumborum (LL) and triceps brachii (TB) muscles were determined. The content of fatty acids in the subcutaneous fat of the loin as well as in the raw LL and TB muscles was estimated as well. It was shown that there were no significant differences in the range of slaughter value traits and meat quality between the groups. However, it was found that different kinds of supplemented fat had a different effect on the content of the polyunsaturated fatty acids in the backfat and in the raw LL muscle. The lowest level of fatty acids characterized the group of pigs fed with supplements consisting of rapeseed and fish oils + lard. The highest values were detected among fatteners supplemented with linseed. The kind of supplemented fat affected the changes in the level of PUFA n-3 fatty acids, especially the linolenic acid C18:3 in backfat. The n-6/n-3 ratio in pigs fed with a greater share of linseed (C and D groups) was better (about 3) than in pigs which obtained a greater portion of rapeseed and fish oils (about 5.5). In both the muscles and fat of fatteners from groups B and C the DHA content was 2-3 times higher than in A and D groups. Higher EPA content was found in the TB muscle.